A systematic literature review of budget participation: foundations, trends, and ways forward - Yousif Alhasnawi, Mushtaq; Mohd Said, Ridzwana; Raad Muhsen, Yousif; Alnoor, Alhamzah; Mowafaq Alshdaifat, Sajead; Mohamed El Shlmani, Zahra (Taylor and Francis Ltd., 2024)
This research aims to extend existing knowledge by conducting a systematic literature review (SLR) on budget participation (BP). A total of 118 articles were collected from three reliable datasets: Web of Science, Scopus, and ScienceDirect (1999–2023). The main items reviewed in this systematic review include existing theories, antecedents and consequences of BP, methodologies (analysis techniques, sample size, and sector), and regions of publication. The SLR revealed that various theories have been used to support hypotheses, and the majority of the articles used goal-setting theory. The analysis also shows that little attention has been given to antecedents, while most researchers focused on the consequences of budget participation. Most previous studies have been based on limited sample size, and there is a dearth of research on BP in certain regions, and structural equation modeling techniques were the most used research methodologies.